Toward a geography of black internationalism: Bayard Rustin, nonviolence and the promise of Africa - Hodder, Jake (Taylor & Francis, 2016)
This article charts the trip made by civil rights leader Bayard Rustin to West Africa in 1952, and examines the unpublished ‘Africa Program’ which he subsequently presented to leading American pacifists. I situate Rustin’s writings within the burgeoning literature on black internationalism which, despite its clear geographical registers, geographers themselves have as yet made only a modest contribution towards. The article argues that within this literature there remains a tendency to romanticize cross-cultural connections in lieu of critically interrogating their basic, and often competing, claims. I argue that closer attention to the geographies of black internationalism, however, allows us to shape a more diverse and practiced sense of internationalist encounter and exchange. The article reconstructs the multiplicity of Rustin’s black internationalist geographies which drew eclectically from a range of Pan-African, American and pacifist traditions. Though each of these was profoundly racialized, they conceptualized race in distinctive ways and thereby had differing understandings of what constituted the international as a geographical arena. By blending these forms of internationalism Rustin was able to promote a particular model of civil rights which was characteristically internationalist in outlook, nonviolent in principle and institutional in composition; a model which in selective and uneven ways continues to shape our understanding of the period.